Analisis Pendekatan Realistic Mathematic Education dalam Pemahaman Pembelajaran Bangun Datar Siswa Kelas 3 SD - Unaenah, Een; Septiani, Amalia; Nurfadilah, Nurfadilah; Mariyam, Siti (Lembaga Yasin AlSys, 2023)
RME learning is an approach to student-centered mathematics learning that links students to the real world. But in reality, teachers more often use conventional learning. One of the difficulties of students in understanding learning material is influenced by the approach used by the teacher which is still not appropriate and interesting and very influential on student learning outcomes in mathematics. This study aims to: (1) analyze the mathematics learning outcomes of students who use the PMRI application, (2) analyze the mathematics learning outcomes of students who do not use the PMRI application, (3) analyze significant differences in mathematics learning outcomes between those who use and do not use the PMRI application . This study uses a quantitative approach. The type of research used is Quasi Experimental Design, using the Nonequivalent Control Group Design quasi experimental design. The population in this study were 40 students in class III at SDN JURUMUDI 4. Sampling using total sampling technique is a sampling technique in which all members of the population are taken as a sample. The sample in this study were 20 students in class III A as the control class and 20 students in class III B as the experimental class. Data analysis of the results of this study used the Malnn-Whitney test. Based on the data analysis that has been done by the researcher, it can be concluded that: (1) The mathematics learning outcomes of third grade students at SDN JURUMUDI 4 who use the PMRI application have an average of 82. (2) The mathematics learning outcomes of third grade students at SDN JURUMUDI 4 who not using PMRI implementation has an average of 58.65. (3) There is a significant difference in mathematics learning outcomes in class III students at SDN JURUMUDI 4 between those who use and do not use the PMRI application. The results of the analysis show a significant value of 0.00 <0.05, so H0 is rejected. It can be concluded that the mathematics learning outcomes of students who were taught using PMRI were better than the mathematics learning outcomes of students who were not taught using PMRI.